Respuesta :

zdhe

Answer:

24w - 21

Step-by-step explanation:

-8(2 - 3w) - 5

We first expand the -8

-16 + 24w - 5

We then add -16 to -5

-16 + -5

= -21

We get the 24w, put in in the equation and get 24w - 21

Answer:

24w−21

Step-by-step explanation:

Factoring  24w2+10w-21

The first term is,  24w2  its coefficient is  24 .

The middle term is,  +10w  its coefficient is  10 .

The last term, "the constant", is  -21

Step-1 : Multiply the coefficient of the first term by the constant   24 • -21 = -504

Step-2 : Find two factors of  -504  whose sum equals the coefficient of the middle term, which is   10 .

     -504    +    1    =    -503

     -252    +    2    =    -250

     -168    +    3    =    -165

     -126    +    4    =    -122

     -84    +    6    =    -78

     -72    +    7    =    -65

     -63    +    8    =    -55

     -56    +    9    =    -47

     -42    +    12    =    -30

     -36    +    14    =    -22

     -28    +    18    =    -10

     -24    +    21    =    -3

     -21    +    24    =    3

     -18    +    28    =    10    That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -18  and  28

                    24w2 - 18w + 28w - 21

Step-4 : Add up the first 2 terms, pulling out like factors :

                   6w • (4w-3)

             Add up the last 2 terms, pulling out common factors :

                   7 • (4w-3)

Step-5 : Add up the four terms of step 4 :

                   (6w+7)  •  (4w-3)

            Which is the desired factorization